2016
DOI: 10.1016/j.tate.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A literature review on how need-supportive behavior influences motivation in students with sensory loss

Abstract: h i g h l i g h t sNeed-support is important in the education of students with sensory loss. Structure is the most studied dimension of need-support. All studies on structure provide examples of need-supportive teaching. Fewer studies address teachers' autonomy support and involvement. For autonomy and involvement also examples of need-thwarting are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…However, research on students with special educational needs is scarce. A literature study on students with visual impairments, hearing impairments, and deafblindness showed that the theoretical framework of SDT as a whole has never been applied in the education of students with sensory loss (see Haakma et al, 2016a). To fill this research gap, we started studying the application of SDT in the education of students with deafblindness.…”
mentioning
confidence: 99%
“…However, research on students with special educational needs is scarce. A literature study on students with visual impairments, hearing impairments, and deafblindness showed that the theoretical framework of SDT as a whole has never been applied in the education of students with sensory loss (see Haakma et al, 2016a). To fill this research gap, we started studying the application of SDT in the education of students with deafblindness.…”
mentioning
confidence: 99%
“…A number of specific SDT-based interventions have been developed but not tested in an ADHD population (see for some recent e.g., Aelterman et al, 2013Aelterman et al, , 2014Aelterman et al, , 2016Haakma et al, 2016). Su and Reeve (2011) performed a meta-analysis on 19 studies that examined the effects of intervention programs explicitly focused on autonomy support.…”
Section: Discussionmentioning
confidence: 99%